Altman Z-Score Sebagai Pengukur Potensi Kebangkrutan PT. MNC Land Sebelum Dan Selama Pandemi Covid-19 - I Gusti Dwiyanti; A.A. Maheswari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
MNC Land, as one of the companies engaged in the hotel accommodation sector, has also experienced a negative impact due to the pandemic. The income statement shows a decrease in the revenue account of PT. MNC Land. If the COVID-19 pandemic lasts for a long time, it will have the potential to cause bankruptcy. Assessment of the potential bankruptcy prediction of the company can be measured through the Altman Z-Score analysis model. This study aims to assess the potential for bankruptcy of PT. MNC Land before and during the COVID-19 pandemic when measured by the Altman Z-Score model. The calculation results show that before COVID-19 spread to Indonesia (2017 – 2019) and during the pandemic (2020), PT. MNC Land Tbk is in a safe discriminant zone. The company is still in a healthy state and does not have financial problems or has no potential for bankruptcy.